2019
DOI: 10.1021/acs.biomac.8b01836
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Lipopeptide-Based Antibacterial Hydrogel

Abstract: A biocompatible hydrogel containing a hexapeptide as a key unit has been designed and fabricated. Our design construct comprises a β-sheet-rich short hexapeptide in the center with a hydrophobic long chain and hydrophilic triple lysine unit attached at the N- and C-terminals, respectively. Thus, it is this amphiphilic nature of the molecule that facilitates gelation. It can capture solvent molecules in the three-dimensional cross-linked fibrillar networks. The amphiphilic character of the construct has been mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…The hydrogel showed efficacy as a neuroprotectant against anti-NGF-induced toxicity. In conclusion, the study proposed the good application potential of the hydrogel for delivery of hydrophobic drugs in the brain, particularly for patients of Alzheimer's disease and brain tumors (Adak et al, 2017 andAdak et al, 2019).…”
Section: Lipopeptide-based Nanohydrogel In Brain Drug Deliverymentioning
confidence: 88%
“…The hydrogel showed efficacy as a neuroprotectant against anti-NGF-induced toxicity. In conclusion, the study proposed the good application potential of the hydrogel for delivery of hydrophobic drugs in the brain, particularly for patients of Alzheimer's disease and brain tumors (Adak et al, 2017 andAdak et al, 2019).…”
Section: Lipopeptide-based Nanohydrogel In Brain Drug Deliverymentioning
confidence: 88%
“…This hydrogel was able to disrupt cell membranes, including the outer membrane of Gram-negative bacteria, resulting in cell death. 61 …”
Section: Linking Self-assembly Mechanical and Antimicrobial Properties Of Peptide Hydrogelsmentioning
confidence: 99%
“…Coil29 (QARILEADAEILRAYARILEAHAEILRAQ-NH 2 ) Ovalbumin 257-264 3B [121] PADRE (aKXVAAWTLKAa) 3B [121] PEPvIII (LEEKKGNYVVTDH) 3B [121] PEPvIII (LEEKKGNYVVTDH)/ PADRE (aKXVAAWTLKAa) 3B [121] Ovalbumin 323-339 3B [122] E214 (Ac-KFEGTEDAVETIIQAIEA) 3B [122] Ac-(Leu) 15 -Lys J8 (Ac-QAEDKVKQSREAKKQVEKALKQLEDKVQ)/ PADRE (AKFVAAWTLKAAA-NH 2 ) 3B [123] Ac-KKFKFEFEF Tyrosinase-related protein 2 180-188 3B [124] P10 (D[KIEKRIK] 5 KWWP) LSEIKGVIVHRLEGFFLLTRILTIPQSLD/gonadotropinreleasing hormone 3B [125] STQNAIDEITNKVN 3B [125] FF03 QVVHNSYNRPAYSPG 3B [126] AP205 SpyTag/Pfs25 3B [127] Mi3 SpyCatcher/cysteine-rich protective antigen 3B [128] SAPNs αTSR/ NANP/flagellin 3B [129] Matrix protein 2/HelixC 3B [130] P27/P27A 3B [131] Ac-AAVVLLLW Human papillomavirus E7 43-57 3B [132] Lumazine synthase nanoparticles Z-domain of protein A from Aquifex aelicus/ anti-HER2 antibodies/fluorescein 3B [133] AlDox (6-maleimidocapryl hydrazone) 3B [133] Sialic acid/Alexa Fluor 488 3F [134] Polyhedron protein from Autographa californica nucleopolyhedrovirus nanoparticles Open reading frame 2 from Porcine Circovirus Type 2 3B [135] NAVISQKKK-NH 2 KKK 3C [136] Ac-K 6 (SL) 6 K 6 -NH 2 Lysine residues 3C [137] Ac-WK x (QL) y K z -NH 2 Lysine residues 3C [138][139][140] Ac-WK 2 (QL) 6 K 2 -NH 2 /Ac-H 3 (QL) 6 Melittin 3C [141] K 3 W(QL) 6 K 2 -NH 2 Lysine residues/polyethylene glycol 3C [142] Fmoc-FFE Spermine 3C [143] Nap-FFE Spermine 3C [143] Nap-FFKK Lysine residues 3C [144] FFKK Naproxen 3C [145] Nap-FFFKK Lysine residues 3C …”
Section: Assembly Motif Display Motif Section Referencesmentioning
confidence: 99%
“…[30,33,318] A multivalent display of high density of positive charge on supramolecular peptide materials is often obtained by appending multiple lysine residues to self-assembling sequences. [144,148] Adak et al [136] have demonstrated the effectiveness of appending a triple lysine sequence to an amphiphilic self-assembling peptide (NAVISQKKK) to form an antibacterial hydrogel that was not-cytotoxic toward mammalian cells. Sarkar et al [137] similarly described a self-assembled peptide-based hydrogel with multiple lysine residues that was an effective antibacterial against Gram-negative Pseudomonas aeruginosa.…”
Section: Antimicrobial Materialsmentioning
confidence: 99%
See 1 more Smart Citation